Styrax, emperor's cream from the Western Regions - Tianwen Yao; Baican Yang (Wolters Kluwer Health/LWW, 2018)
Styrax is also called "emperor's cream" and "consciousness-regaining spice." The alias "emperor's cream" shows its rarity and preciousness with a strong aroma, and another name of "consciousness-regaining spice" implies its functions of active brain and regaining consciousness, dispelling filth with aroma, and relieving pain. The name of "Styrax" displays its complex productive progress and place of origin. With thick quality, heavyweight, and fragrant smesll, Styrax gets further application in beauty, skin care, clothes fumigating, and health keeping after introduced into the Central Plains (central China) from the Western Regions. The name of Styrax not only embodies the mellow appeal of spice culture in the Western Regions but also suggests the history of relationship between foreign culture and traditional Chinese medicine. Furthermore, it indicates the broad mind of "all rivers running into sea" and inclusiveness of Chinese culture.